Blood Vessels and Myocardial Thickness within the Left Atrial Appendage Isthmus Line. Issue 7 (26th October 2018) - Hołda, Mateusz K.; Hołda, Jakub; Strona, Marcin; Koziej, Mateusz; Klimek‐Piotrowska, Wiesława
Abstract : Electric isolation of the left atrial appendage (LAA) and linear ablations in the area of the LAA base are gaining popularity. However, very little is known about the myocardial architecture and the presence of epicardial blood vessels within this region, which could significantly influence the course of such procedures. We examined 200 autopsied hearts (22.5% females, 46.7 ± 16.8 years old). The LAA isthmus (i.e., the line between the LAA ostium and the mitral annulus) was cut longitudinally. The myocardium was thickest at the LAA end of the isthmus (2.4 ± 0.7 mm) followed by its middle sector (2.1 ± 0.7 mm) inside the LAA, 5 mm from its ostium (1.9 ± 0.7 mm), and the mitral annulus end of the isthmus (1.8 ± 0.6 mm) ( P  < 0.0001). At least one artery was found in 96.5% of all samples (89.5% were single branched, 7% had two branches). The great cardiac vein was found in 77.0% and the left marginal vein in 2.5%. The artery was interposed between the endocardium and the great cardiac vein in 31.5% of cases. The smallest distance between the endocardium and the artery was 0.5 mm and between the endocardium and the vein was 0.7 mm. In total, we were able to distinguish fifteen different types of vascular arrangements within the LAA isthmus line in this study. The myocardium within the LAA isthmus is thickest at its LAA end. The left circumflex coronary artery branches are the most frequently‐occurring vessels within the isthmus and are present in almost all cases, while the great cardiac vein is present in three quarters of hearts. Clin. Anat. 31:1024–1030, 2018. © 2018 Wiley Periodicals, Inc.